2017
DOI: 10.21037/jtd.2017.09.139
|View full text |Cite
|
Sign up to set email alerts
|

Airway stent complications: the role of follow-up bronchoscopy as a surveillance method

Abstract: Background: Airway stenting has become an integral part of the therapeutic endoscopic management of obstructive benign and malignant central airway diseases. Despite increased use of airway stents and frequent stent-associated complications, no clear guidelines for surveillance and maintenance exist. This study aim is to elucidate predictive factors associated with development of stent complications, as well as an optimal surveillance period for follow-up bronchoscopy for early detection and possible preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…Further follow-up and repeat bronchoscopy will depend on the patient’s clinical status and underlying disease 27. Lee et al provided similar immediate postoperative care management for patients with tracheobronchial stenting, with follow-up bronchoscopy between 4 and 6 weeks when stable or urgent bronchoscopy when symptomatic 28. In comparison, our centre encourages early extubation, mobilisation, chest physiotherapy and nebulised saline therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Further follow-up and repeat bronchoscopy will depend on the patient’s clinical status and underlying disease 27. Lee et al provided similar immediate postoperative care management for patients with tracheobronchial stenting, with follow-up bronchoscopy between 4 and 6 weeks when stable or urgent bronchoscopy when symptomatic 28. In comparison, our centre encourages early extubation, mobilisation, chest physiotherapy and nebulised saline therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Migration behaviors observed in clinical practices [22,23] were not considered in this work. It has been shown that a larger radial/bending strength, correlated with higher contact force between stent and the lesion, could mitigate the migration of a straight stent [24].…”
Section: Discussionmentioning
confidence: 99%
“…One study with 16 patients did not register deaths associated with the stents and their removal was feasible in all the cases reported [31]. In a more recent study with 30 patients there were no associated deaths and successful removal was achieved in 90% of cases [32]. These studies show the feasibility and safety of these new stents, though a comparative study with the silicone stent as the gold standard is needed to draw robust conclusions.…”
Section: Stentsmentioning
confidence: 99%